2017
DOI: 10.1007/s12038-017-9680-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dynamin family proteins by post-translational modifications

Abstract: Dynamin superfamily proteins comprising classical dynamins and related proteins are membrane remodelling agents involved in several biological processes such as endocytosis, maintenance of organelle morphology and viral resistance. These large GTPases couple GTP hydrolysis with membrane alterations such as fission, fusion or tubulation by undergoing repeated cycles of self-assembly/disassembly. The functions of these proteins are regulated by various post-translational modifications that affect their GTPase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…The large scale phosphoproteomic screens have identified multiple tyrosine phosphorylation sites of DYNAMIN, such as that occurring at pY 80 , pY 125 , pY 354 and pY 597 (Ballif et al, 2008) (Mallozzi et al, 2013). Among them, the Y 597 was a wellstudied phosphorylation site of DYNAMIN, which was previously reported to increase selfassembly and GTP hydrolysis in both DYNAMIN1 and 2 (Kar et al, 2017). However, the Y 597 of DYNAMIN was probably not the target of PTP-MEG2 because the interaction of Y 597 or A 597 with PTP-MEG2 exhibited no significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large scale phosphoproteomic screens have identified multiple tyrosine phosphorylation sites of DYNAMIN, such as that occurring at pY 80 , pY 125 , pY 354 and pY 597 (Ballif et al, 2008) (Mallozzi et al, 2013). Among them, the Y 597 was a wellstudied phosphorylation site of DYNAMIN, which was previously reported to increase selfassembly and GTP hydrolysis in both DYNAMIN1 and 2 (Kar et al, 2017). However, the Y 597 of DYNAMIN was probably not the target of PTP-MEG2 because the interaction of Y 597 or A 597 with PTP-MEG2 exhibited no significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that phosphorylation of DYNAMIN close to the G domain significantly increased its GTPase activity, thus promoting endocytosis (Kar et al, 2017). We therefore hypothesized that the phosphorylation of the DYNAMIN2 pY 125 site increased pore fission by up-regulating its GTPase activity, whereas dephosphorylation of DYNAMIN2 pY 125 site by PTP-MEG2 reversed it.…”
Section: Dynamin2-py 125mentioning
confidence: 91%
“…miR‐1 targets PTH and IL‐6 and it has crucial functions in the development and physiology of muscle tissue 36,37 ; one of his target is Dynamin3 , that is reported as the most downregulated gene in GSD‐osteoclasts array 15 . Dynamin 3 is an ubiquitin ligase that regulates microtubule dynamics and cell division 38 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated that members of the Dynamin family also function as molecular switches, similar to the classical signal GTPase [22]. A common feature of all dynamins and dynamin-related proteins is the presence of a GTPase effector domain (GED), a middle domain (MD), and a large N-terminal GTPase domain [23].…”
Section: Introductionmentioning
confidence: 99%